Importance of Land Snails in Dicrocoeliosis Epidemiology - Gürelli, Gözde (Galenos Yayinevi, 2017)
Dicrocoeliosis is a helminthosis caused by the small liver fluke Dicrocoelium spp. (Trematoda, Dicrocoeliidae) parasitizing in the bile ducts and gall bladder of ruminants as well as many other animal species including humans. In the biological life cycle of Dicrocoelium, land snails are first intermediate hosts and ants are second intermediate hosts. Sporocysts and cercaria, which are larval stages, live in the hepatopancreas of land snails and metacercaria, which is also the larval stage, lives in the abdomen and brain of ants. Land snails, which are the first intermediate host of this parasite in Turkey, include Helicopsis derbentina, Helicopsis protea, Helicopsis krynickii, Cernuella virgata, Trochoidea pyramidata, Cochicella acuta, Monacha carthusiana, Helicella candicans, Helix aspersa, Helix lucorum, and Chondrus tournefortianus. Dicrocoeliosis is widespread in ruminants and affects their liver, which can lead to weight loss and reduced milk production. The number of reports on dicrocoeliosis is increasing due to the expansion of dry habitats and parasites becoming resistant to antihelminthic drugs. This study provides information on the epidemiology and control methods of Dicrocoelium.
Keywords: Turkey; Ants; Helix, Snails; Animals; Humans; Dicrocoeliasis; Dicrocoelium; Host-Parasite Interactions; 3. Good health